11 - Le chemin de l’autodestruction: origine et dynamique de la guerre civile en Côte d’Ivoire: DOI: 10.4314/ad.v30i1.22220 - Ogunmola, Dele; Badmus, Isiaka Alani (Africa Development, 2005)
This article contends that colonial history and heritage coupled with an ill-managed Houphouët legacy have led to the crisis in Côte-d'Ivoire. The economic crisis that followed the period of economic prosperity resulted in the harming of the patrimonial system, thus leading to a shattering of the Ivorian society. The crisis that is occur ring around the Ivorian identity is based on ethnic, as well as religious grounds, and has led to a military and political stalemate. Ivorians must demonstrate an authentic and patriotic reaction, as well as collective and pragmatic political will, in order to support the international mediation aiming at settling the conflict in a peaceful way.